2005
DOI: 10.1002/14651858.cd002273.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Air versus oxygen for resuscitation of infants at birth

Abstract: Characteristics of included studies [ordered by study ID] Methods Concealment of allocation: No-quasi-randomised by date of birth (even dates=room air, odd dates=100% oxygen) Blinding of intervention: No Completeness of followup: Yes for short-term outcomes-100% followup for in-hospital outcomes but No for outcomes at 28 days (86%) Blinding of outcome measurement: No Participants Single centre study. 84 neonates with apnoea and/or heart rate < 80 bpm and a birth weight > 999 g. Interventions Room air (n=42) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(34 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Indeed, neonatal resuscitation with room air seems to be as effective as 100% oxygen and may even be associated with reduced mortality rates. 57,58 Regarding pulmonary outcomes, the authors of 2 early-oxygen studies reported a reduced risk of chronic lung disease with low oxygen saturations, 10,14 a finding that was confirmed by a cohort study on bronchopulmonary dysplasia. 59 …”
Section: Discussionmentioning
confidence: 90%
“…Indeed, neonatal resuscitation with room air seems to be as effective as 100% oxygen and may even be associated with reduced mortality rates. 57,58 Regarding pulmonary outcomes, the authors of 2 early-oxygen studies reported a reduced risk of chronic lung disease with low oxygen saturations, 10,14 a finding that was confirmed by a cohort study on bronchopulmonary dysplasia. 59 …”
Section: Discussionmentioning
confidence: 90%
“…In a Cochrane meta-analysis of studies comparing resuscitation with 100% oxygen to resuscitation with room air in term and near term infants, resuscitation performed with room air resulted in lower mortality than in those resuscitated with 100% oxygen (RR=0.71]). 70 However, among preterm infants the role of supplemental oxygen therapy in the delivery room is less clear. In a RCT of room air versus oxygen administration for the delivery room resuscitation of preterm infants less than 32 weeks gestation (ROAR study), there was no difference in the outcomes of BPD or death among infants treated with either room air, titrated oxygen therapy or those who received static 100% oxygen.…”
Section: Risk Factors After Birthmentioning
confidence: 99%
“…In addition, the immature kidneys are abruptly exposed to high oxygen (O 2 ) concentrations relative to the intrauterine environment through ventilation and supplemental oxygen therapy (21–100% O 2 is utilised[9]), with arterial blood oxygen saturation rapidly increasing after birth [10]. These high O 2 concentrations are known to impact hypoxia inducible factor (HIF)-1α levels and subsequently downregulate the expression of vascular endothelial growth factor (VEGF) [11, 12] which is essential for glomerular capillary growth and development [13, 14].…”
Section: Introductionmentioning
confidence: 99%